Robust bulk micro-nano hierarchical copper structures possessing exceptional bactericidal efficacy. (January 2022) - Smith, J.L.; Tran, N.; Song, T.; Liang, D.; Qian, M.
Abstract: Conventional copper (Cu) metal surfaces are well recognized for their bactericidal properties. However, their slow bacteria-killing potency has historically excluded them as a rapid bactericidal material. We report the development of a robust bulk superhydrophilic micro-nano hierarchical Cu structure that possesses exceptional bactericidal efficacy. It resulted in a 4.41 log10 reduction (>99.99%) of the deadly Staphylococcus aureus ( S . aureus ) bacteria within 2 min vs. a 1.49 log10 reduction (96.75%) after 240 min on common Cu surfaces. The adhered cells exhibited extensive blebbing, loss of structural integrity and leakage of vital intracellular material, demonstrating the rapid efficacy of the micro-nano Cu structure in destructing bacteria membrane integrity. The mechanism was attributed to the synergistic degradation of the cell envelope through enhanced release and therefore uptake of the cytotoxic Cu ions and the adhesion-driven mechanical strain due to its rapid ultimate superhydrophilicity (contact angle drops to 0° in 0.18 s). The scalable fabrication of this micro-nano Cu structure was enabled by integrating bespoke precursor alloy design with microstructure preconditioning for dealloying and demonstrated on 2000 mm 2 Cu surfaces. This development paves the way to the practical exploitation of Cu as a low-cost antibiotic-free fast bactericidal material.